2018
DOI: 10.1096/fj.201700473rr
|View full text |Cite
|
Sign up to set email alerts
|

USP7‐TRIM27 axis negatively modulates antiviral type I IFN signaling

Abstract: Ubiquitination and deubiquitination are important post-translational regulatory mechanisms responsible for fine tuning the antiviral signaling. In this study, we identified a deubiquitinase, the ubiquitin-specific peptidase 7/herpes virus associated ubiquitin-specific protease (USP7/HAUSP) as an important negative modulator of virus-induced signaling. Overexpression of USP7 suppressed Sendai virus and polyinosinic-polycytidylic acid and poly(deoxyadenylic-deoxythymidylic)-induced ISRE and IFN-β activation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 77 publications
1
40
0
Order By: Relevance
“…Previous studies have shown that TRIM family proteins play important roles in transcriptional control, viral suppression, energy metabolism, development and cellular differentiation, immune response, proliferation, cancer and genome stability, etc Results from others and our group have shown that tripartite motif‐containing 28 (TRIM28) mediates the differentiation of murine embryonic stem cells into cardiomyocytes, angiogenesis, and endothelial inflammatory response . Tripartite motif‐containing 27 (TRIM27) is involved in cell proliferation and transcriptional repression . In this study, we identified that TRIM28 and TRIM27 cooperatively regulate the phenotypic switching through a novel mechanism involving serum response element (SRE) in human VSMCs.…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies have shown that TRIM family proteins play important roles in transcriptional control, viral suppression, energy metabolism, development and cellular differentiation, immune response, proliferation, cancer and genome stability, etc Results from others and our group have shown that tripartite motif‐containing 28 (TRIM28) mediates the differentiation of murine embryonic stem cells into cardiomyocytes, angiogenesis, and endothelial inflammatory response . Tripartite motif‐containing 27 (TRIM27) is involved in cell proliferation and transcriptional repression . In this study, we identified that TRIM28 and TRIM27 cooperatively regulate the phenotypic switching through a novel mechanism involving serum response element (SRE) in human VSMCs.…”
Section: Introductionmentioning
confidence: 78%
“…USP7 interacts with TRIM27 and forms the USP7-TRIM27-TBK1 complex, and the interaction between USP7 and TRIM27 can be enhanced after Sendai virus (SeV) infection. When USP7 was overexpressed, TRIM27 can be protected from degradation, which contributed to the ubiquitination and degradation of TBK1, resulting in decreased type I interferons (IFNs) signaling (Cai et al, 2018). As IFNs are a series of signaling proteins which are produced and released by host cells to cope with the presence of pathogens, USP7 can enhance the effects of TRIM27 on TBK1-induced IFN – stimulated response element (ISRE) and IFN-β activation (Zaman et al, 2013).…”
Section: Usp7: One Protein Multiple Rolesmentioning
confidence: 99%
“…USP7 was found to bind and remove ubiquitin from TRIM27 allowing for the ubiquitination and degradation of TBK1 (Fig. 6) [159].…”
Section: Negative Regulation Of Host Antiviral Signallingmentioning
confidence: 99%